Pengaruh Pemberian Kredit Usaha Mikro terhadap Potensi Pengembangan Usaha Nasabah Pegadaian Syariah Pekanbaru: The Effect of Providing Micro Business Credit on the Business Development Potential of Pekanbaru Sharia Pawnshop Customers - Zulfa, Marina (QULUBANA: Jurnal Manajemen Dakwah, 2024)
Sharia pawnshops provide an alternative to obtain sources of funds and financing to meet financial needs. One of the products they offer is called "Ar Rum," which provides financing solutions for small businesses by using car BPKB as collateral. The subject of the study is small business people in the city of Pekanbaru, and the object in this study is the effect of providing micro business loans on the business development potential of sharia pawnshop customers. The data collection techniques used are Observation, Questionnaire and Documentation. Based on a simple linear regression analysis hypothesis test through SPSS for Windows version 25.0, in the regression equation, the value of consta (a) is 2.524, meaning that if the provision of micro business credit is assumed to be zero (0) then (Y) is 2.674 and the value of the variable regression coefficient (X1) is 0.645. This means that every decrease in micro business lending by 1 unit will decrease (Y) by 0.465. In the Partial Test (t-Test) the value of t calculate the variable (X1) of 15.571 and the value of t table of 2.048 with a significant level of 0.05 and a degree of freedom of 30 (dk = n-k-1(30-1-1)) it will be seen that: tcalculate > t table or 15.571 > 2.048. This shows that Ha was accepted and Ho was rejected with a significant level of 0.05 where the value (Sig) was 0.000 < 0.05 so that it can be said that there is a significant influence between Micro Business Lending on Business Development Potential.